Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.


Given f(x) = 2x2 – 9x + 2, g(x) = 1 - 6x, and
h(x) = x2 – 4, find the following function:
(h+f)(x)


Sagot :

Answer:

[tex](h+f)(x)=3x^2-9x-2[/tex]

Step-by-step explanation:

[tex]f(x)=2x^2-9x+2\\g(x)=1-6x\\h(x)=x^2-4[/tex]

Looks like g(x) is irrelevant here.

You can expand this like so:

[tex](h+f)(x)\\h(x)+f(x)[/tex]

And even further:

[tex](x^2-4)+(2x^2-9x+2)[/tex]

Now, it's just a matter of simplifying.

[tex]x^2-4+2x^2-9x+2\\\\(x^2+2x^2)+(-9x)+(-4+2)\\\\3x^2-9x-2[/tex]

Therefore:

[tex](h+f)(x)=3x^2-9x-2[/tex]